Paralympic powerlifting as a sustainable way to improve strength in athletes with spinal cord injury and other disabilities - Aidar, Felipe J. (2022)
Background: in Paralympic Powerlifting (PP), athletes with a spinal cord injury (SCI) and other disabilities (OD) compete together. However, athletes with SCI are at a disadvantage in terms of force production and transfer. Objective: to analyze the strength and the dynamic and static indicators, at different intensities, tied and untied in athletes with SCI and OD. Methods: the sample presented 10 OD (28.30 ± 4.92 years) and 10 SCI (30.00 ± 4.27 years), classified competitors, and eligible to compete in the sport (all males). Maximum isometric force (MIF); time to MIF (Time); rate of force development (RFD); impulse, variability, and fatigue index (FI); and the dynamic tests of Mean Propulsive Velocity (MPV), Velocity Maximum (Vmax), and Power with loads of 40, 60, and 80% of 1 Repetition Maximum (1 RM), respectively. Results: there were no differences between OD and SCI in dynamic and isometric strength indicators. In MPV, there was an 80% difference between tethered and untethered SCI (p = 0.041). In VMax, there were differences in SCI between tethered and untethered, 40% (p = 0.004) and 80% (p = 0.023), respectively. There were no differences in the other intensities. Conclusion: PP training seems to be a sustainable way to promote strength gains in SCI, since there were no differences between athletes with SCI and OD, as practitioners of Paralympic Powerlifting.